Novel di and tripeptide side groups bearing acrylate polymers: synthesis, characterization, and their theoretical, and electrical properties - Koran, Kenan (Springer, 2022)
In this study, the kinetic and dielectric properties of new acrylate polymers containing dipeptide and tripeptide side groups were studied. For this purpose, homopolymers containing peptide side groups were obtained through the new acrylate monomers (Tyr(Boc)-Met-OCH3 and Tyr(Boc)-Met-Phe-OCH3) via the free radical polymerization method. The glass transition temperatures (Tg) of polymers were determined as 221.58 and 206.25. The average activation energies of polymers were measured at different heating rates (5, 10, 20, 30 and 40 degrees C min(-1)) and calculated as 136,85 and 118,10 kj mol(-1) based on Flynn-Wall-Ozawa (F-W-O) method, respectively. Theoretical experiments were carried out via density functional theory (DFT). The dielectric parameters of the polymers were determined as a function of frequency, so that, dielectric constant values of homopolymers at 1 kHz calculated as 8.64 and 5.12 and ac conductivities were calculated as 5.27 x 10(-09) S cm(-1) and 3.06 x 10(-09) S cm(-1).
Keywords: Dipeptide; Tripeptide; Homopolymer; Thermal properties; Dielectric properties